The porcine iodoacetic acid model of retinal degeneration: Morpho-functional characterization of the visual system. (April 2020) - Barone, Francesca; Muscatello, Luisa Vera; Ventrella, Domenico; Elmi, Alberto; Romagnoli, Noemi; Mandrioli, Luciana; Maya-Vetencourt, Josè Fernando; Bombardi, Cristiano; Mete, Maurizio; Sarli, Giuseppe; Benfenati, Fabio; Pertile, Grazia; et al.
Abstract: Porcine models of ophthalmological diseases are often used in pre-clinical translational studies due to pigs' similarities to humans. In particular, the iodoacetic acid (IAA) model of photoreceptor degeneration seems to mimic well the endstage phenotype of human pathologies as retinitis pigmentosa and age-related macular degeneration, with high potential for prosthesis/retinal devices testing. IAA is capable of inducing photoreceptor death by blockage of glycolysis, and its effects on the retina have been described. Nonetheless, up to date, literature lacks of a comprehensive morpho-functional characterization of the entire visual system of this model. This gap is particularly critical for prosthesis testing as inner retinal structures and optic pathways must be preserved to elicit cortical responses and restore vision. In this study, we investigated the functional and anatomical features of the visual system of IAA-treated pigs and compared them to control animals. IAA was administered intravenously at 12 mg/kg; control animals received saline solution (NaCl 0.9% w/v). Electrophysiological analyses included full-field (ffERGs) and pattern (PERGs) electroretinograms and flash visually evoked potentials (fVEPs). Histological evaluations were performed on the retina and the optic pathways and included thickness of the different retinal layers, ganglion cells count, and immunohistochemistry for microglial cells, macroglial cells, and oligodendrocytes. The histological results indicate that IAA treatment does not affect the morphology of the inner retina and optic pathways. Electrophysiology confirms the selective rod and partial cone degeneration, but is ambiguous as to the functionality of the optic pathways, seemingly preserved as indicated by the still detectable fVEPs. Overall, the work ameliorates the characterization of such rapid and cost-effective model, providing more strength and reliability for future pre-clinical translational trials. Highlights: Iodoacetic acid (12 mg/kg) does not alter the morphology of the inner retina and optic pathways. Functionality of the optic pathway seems to be impaired as confirmed by weak residual flash visually evoked potentials. This photoreceptor degeneration model seems to be suitable for retinal prosthesis preclinical testing.